The Implementation of Character Education in Motto Amuntai the City of Piety in Islam Integrated Elementary School (SDIT) Ihsanul Amal - Ridhatullah Assya'bani; Husin Husin; Munawarah Munawarah (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
This study aimed to examine the implementation of the character education values ​​contained in Amuntai city’s motto “BERTAKWA (Piety)” at SDIT Ihsanul Amal. The main problem that drove this study was that the school's vision and mission are very rarely related to the regional motto, especially in implementation of the teaching and learning process. The research method was a qualitative approach and with an interview, observation, and documentation techniques. The results showed that the implementation of Amuntai city’s motto “BERTAKWA” could shape the character of employees and students at SDIT Ihsanul Amal, practicing the values in the acronym “BERTAKWA” which stands for Bersih (clean), Tertib (orderly), Anggun (elegant), Kompak (unified) and Berwibawa (dignified). The implementation of the character education could be seen from not only in term of theory of learning in the classroom but also a routine in the school environment by familiarizing the students to maintain cleanliness, order, cooperation through habituation activities, and good quality management to be an excellent school.